TEACHING REFERENCE WORD WITH “ROBINHOOD” READING ACTIVITY - Purnawati, Purnawati (English Education:Journal of English Teaching and Research, 2017)
Reading plays a very significant role in the teaching and learning of English as a Second or fereign Language ( ESL/ EFL ) in Junior High School. In fact, it is a mojor skill which has been tested for years in the National Final Examination. The questions which had appeared in the test are mostly testing the students’ reading comprehension ability. To succeed the test , the students should master five genres of monologue text and nine short functional texts. Consequently, teachers should provide them with reading comprehension strategies. This paper offers a strategy “ Inferring anaphoric & cataphoric” Reference with the theoretical assumption of “Think Aloud” through an activity called “ Robinhood” to provide students with a reading strategy to deal with one of the short functional text that is Reference Word. The activity of “Robinhood” will ease them when they are dealing with questions related with reference word.The activity leads students to learn in joyful atmoshere since while learning they also feel like playing a game. Considering the effectiveness of the learning activity, English language teachers are recommended to adopt it in their classes.